Utilization of Dried Bamboo Shoots for Strengthening Women's Economic Empowerment in Bokak Sembumbung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Implementation activity field was done in a way gradually in Bokak Village Sembumbung with put forward approach participatory. Stage beginning started with the coordination of government villages and local groups of women. To determine time, location, and participant activities. Next, an observation field is carried out to identify the potential availability of bamboo shoots as well as the beginning skills community. Core activities include training implemented in the form of delivery materials and practices, direct processing of bamboo shoots, starting from the cleaning process, boiling, drying, and proper packaging for sale. During implementation, participants pushed for active ask and try directly so that the learning process is ongoing and interactive. Interview done semi-structured with all participants. For deeper information, more deeply related experience, perception, and obstacles faced in utilizing bamboo shoots. Interview done before and after the activity to see the change in understanding and attitude participant to potential economic bamboo shoots. Interview results show that before activities, some big participant Not yet realized the mark economy bamboo shoots optimally, while after training, participants started to understand the business that can be developed. In addition, the interview also revealed the need for continued education, especially in the aspects of marketing and management. A combination of the activity field and interviews. This gives a comprehensive overview of the process and impact of the activity on the empowerment of women in Bokak Sembumbung Village.